Critical Discourse Analysis of Theo Van Leeuwen's Inclussion Theory on Anti-Crime Editorials in Daily Newspapers Pos Kota February 2020 Edition - Bagus Hady Hartanto; Erlina Chamalia Rochmah; Goziyah Goziyah (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2020)
This research aims to describe the author's attitudes and views on the common criminality of Indonesia in recent times, which is embodied in anticriminality. The research focuses on the preaching of the crime that is found in the Postal City daily issue of February 2020 by using a study analysis of the critical discourse of Theo Van Leeuwen. The type of research used in this study is qualitative research using the methods of content analysis. The data source used in this study is criminality news found in the Postal city newspaper February 23, 2020. The research Data uses the five news stories in the City Post's daily newspaper with a theme of criminality. Based on the results of the study it can be concluded that Leeuwen's inclusion strategy was found in the Post Kota newspaper's February issue of 2020 with an anti-criminality theme of seven sentencesthat is (1) assimilation, (2) determinations, (3) dissociation, (4) The identification of, (5) Individualization, (6) identifications, (7) categorisation. Keywords : Inclusion, Criminality, Post Kota, Daily NewsPaper.